Plant Feed Additives as Natural Alternatives to the Use of Synthetic Antioxidant Vitamins on Poultry Performances, Health, and Oxidative Status: A Review of the Literature in the Last 20 Years - Federico Righi; Rosario Pitino; Carmen L. Manuelian; Marica Simoni; Afro Quarantelli; Massimo De Marchi; Eleni Tsiplakou (MDPI AG, 2021)
Plant feed additives (PFA) such as essential oils, extracts, and by-products from plant processing can be included in poultry diets. A total of 39 peer-reviewed articles were selected from the literature published in the last 20 years (2000-2020) comparing PFA antioxidant effects with synthetic antioxidant vitamins (mainly vitamin E) in poultry nutrition. The PFA can be used as an effective nutritional strategy to face poultry's oxidative stress with positive impact also on their productivity and efficiency. They can partially or completely replace antioxidant synthetic vitamins (the latter administered at doses between 150 and 500 mg/kg) in animal diets, sometimes affecting important physiological functions or expressing synergistic effect with the synthetic antioxidants. It is crucial to take into consideration the issues related to the absorption and the metabolism of these additives and their interaction with gut microbiota. However, some form- and dose-dependent negative effects on growth performances are observed.